How, why and under what circumstances does a quality improvement collaborative build knowledge and skills in clinicians working with people with dementia? A realist informed process evaluation - Ian Cameron; Billingsley Kaambwa; Jane Thompson; Kate Laver; Maria Crotty; Monica Cations; Craig Whitehead; Gaery Barbery; Lenore de la Perrelle; Gorjana Radisic; Janna Anneke Fitzgerald; Susan Kurrle (BMJ Open Quality, 2021)
In increasingly constrained health and aged care services, strategies are needed to improve quality and translate evidence into practice. In dementia care, recent failures in quality and safety have led the WHO to prioritise the translation of known evidence into practice. While quality improvement collaboratives have been widely used in healthcare, there are few examples in dementia care.We describe a recent quality improvement collaborative to improve dementia care across Australia and assess the implementation outcomes of acceptability and feasibility of this strategy to translate known evidence into practice. A realist-informed process evaluation was used to analyse how, why and under what circumstances a quality improvement collaborative built knowledge and skills in clinicians working in dementia care.This realist-informed process evaluation developed, tested and refined the programme theory of a quality improvement collaborative. Data were collected pre-intervention and post-intervention using surveys and interviews with participants (n=28). A combined inductive and deductive data analysis process integrated three frameworks to examine the context and mechanisms of knowledge and skill building in participant clinicians.A refined program theory showed how and why clinicians built knowledge and skills in quality improvement in dementia care. Six mechanisms were identified: motivation, accountability, identity, collective learning, credibility and reflective practice. These mechanisms, in combination, operated to overcome constraints, role boundaries and pessimism about improved practice in dementia care.A quality improvement collaborative designed for clinicians in different contexts and roles was acceptable and feasible in building knowledge, skills and confidence of clinicians to improve dementia care. Supportive reflective practice and a credible, flexible and collaborative process optimised quality improvement knowledge and skills in clinicians working with people with dementia.Trial registration numberACTRN12618000268246.